2016
DOI: 10.4103/0975-1475.186371
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of the Ricketts' posteroanterior cephalometry for sex determination using logistic regression analysis in Hispano American Peruvians

Abstract: Background:The Ricketts' posteroanterior (PA) cephalometry seems to be the most widely used and it has not been tested by multivariate statistics for sex determination.Objective:The objective was to determine the applicability of Ricketts' PA cephalometry for sex determination using the logistic regression analysis.Materials and Methods:The logistic models were estimated at distinct age cutoffs (all ages, 11 years, 13 years, and 15 years) in a database from 1,296 Hispano American Peruvians between 5 years and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…The development and introduction into practice of new instrumental methods of patient examination (namely, teleroentgenography), combined with the development of anthropology (namely, craniology), allowed in the combination to create a unique in its kind -a cephalometric analysis, which is a reliable tool in the work of modern orthodontics [33]. Moreover, the results of this study have found application in other areas of medicine, in particular in forensic medicine [30].…”
Section: Introductionmentioning
confidence: 84%
“…The development and introduction into practice of new instrumental methods of patient examination (namely, teleroentgenography), combined with the development of anthropology (namely, craniology), allowed in the combination to create a unique in its kind -a cephalometric analysis, which is a reliable tool in the work of modern orthodontics [33]. Moreover, the results of this study have found application in other areas of medicine, in particular in forensic medicine [30].…”
Section: Introductionmentioning
confidence: 84%
“…Semelhante a outros estudos, foi encontrado um número maior de pessoas do sexo feminino na amostra analisada. Esse resultado pode estar relacionado ao fato das mulheres terem maior preocupação com a estética e a saúde [7][8][9][10][11][12] .…”
Section: Discussionunclassified
“…In addition, the methods of cephalometric analysis are successfully used in forensic medicine as a method of additional identification. Thus, in the work of M. Dmitriev et al [9] proved the success of the use of cephalometric analysis by C. Steiner of Ukrainian boys and girls; I. Perez et al [23] after analyzing databases of 1296 people were able to build logistic models for 6 cephalometric indicators by Rickett's analysis with an accuracy of 60 % to 70 % to identify male Peruvians of Spanish descent.…”
Section: Introductionmentioning
confidence: 99%